(untitled) (Italian Review of Legal History, 2024)
The essay reconstructs the doctrinal controversy relating to a rule of the Zanardelli Code (art. 378) which regulates a particular form of criminal participation: the “complicità corrispettiva” (corresponding complicity). Apparently classifiable as yet another episode of the scientific dispute that has divided criminal lawyers with an orientation of protection of civil rights (inspirators of the code) and the exponents of the new social-defense-oriented positivistic approach to criminal law, the case presents some aspects of originality: on the one hand, in fact, even some jurists directly involved in the codification work share the perplexities surrounding the rule; on the other hand, the criticisms addressed by a young exponent of penal positivism, Scipio Sighele, are not formulated according to the precepts of his own scientific field, but are inspired by the same principles of guarantee proclaimed by the legislator.Despite this singular intersection, the “useless and unjust” art. 378 will ultimately remain in the legal system, but will give rise to many interpretative difficulties, which will engage the jurists throughout the life of the code